Public instruction and demand for Normal school counselors in the Araucanía region during the 19th Century - Turra-Díaz, Omar; Torres Vásquez, Angélica (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article aims to provide knowledge about the teaching performance in the Araucanía region, during the second half of the 19th century, in the context of a state policy that sought to expand Chilean public education in Mapuche territory. This research is based on documentary information, extracted mainly from the reports of the visitors to the schools. It is presented here some data about the training and performance of educators responsible for imparting the first letters in the interethnic educational context. According to the information provided by the sources, the lack of preparation in teaching methods and the lack of educators with formal studies constituted a persistent complaint from Visitors and local authorities, which in turn demanded the presence of Normal school counselors. From this perspective the study expose precedents that allow to understand the foundation of Normal Schools in the territory of the Araucanía, starting over the last decade of century XIX.